2022
DOI: 10.3389/fpls.2022.1055900
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil acidification in tea plantations by long-term use of organic fertilizers and its effect on tea yield and quality

Abstract: Soil acidification in tea plantation seriously reduced the yield and quality of tea. It was an effective method to use organic fertilizer for acidified soil remediation to ensure tea yield and quality. In this study, different fertilizers were used to treat the acidified tea plantation soils for 4 consecutive years to analyze the remediation effect of different fertilizers on acidified soil and their effects on tea yield and quality. The results showed that during the period of 2017-2021, the soil pH value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…When assessing the impact of fertilizer management on tea quality, tea polyphenols, free amino acids, and caffeine contents were typically used as assessment indicators. In this study, free amino acid content increased significantly with compost supply (Table 2), which is in line with the previous results [36,37]. Additionally, polyphenols are what give tea its sour and acerbic tastes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When assessing the impact of fertilizer management on tea quality, tea polyphenols, free amino acids, and caffeine contents were typically used as assessment indicators. In this study, free amino acid content increased significantly with compost supply (Table 2), which is in line with the previous results [36,37]. Additionally, polyphenols are what give tea its sour and acerbic tastes.…”
Section: Discussionsupporting
confidence: 92%
“…The tea quality, as the guarantee of economic benefits, was significantly affected by fertilization managements [36]. When assessing the impact of fertilizer management on tea quality, tea polyphenols, free amino acids, and caffeine contents were typically used as assessment indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Soil pH was measured with a pH meter (PB-10, Sartorius) at a soil to water ratio of 1:2.5, and 5 replicates were used for each sample (Ye et al, 2022). Soil organic matter content was determined by oxidation with potassium dichromate and external heating, and soil cation exchange capacity was determined by neutral ammonium acetate (Wang et al, 2020a).…”
Section: Determination Of Ph Value Organic Matter Content and Cation ...mentioning
confidence: 99%
“…The heavy use of chemical fertilizers can decrease soil pH while the use of organic fertilizers can regulate soil pH. Ye et al (2022) reported that the long-term use of chemical fertilizer led to a continuous decrease in soil pH from 3.07-2.82 in tea plantations in Southeast China while the long-term use of organic fertilizer led to a stable pH of 5.13-5.33, which is suitable for growth, improved yield, and quality of tea. Persistent decreases in soil pH in addition to decreasing microbial diversity, may result in the denaturing of soil enzymes, and lowered nutrient solubility and availability to plants, as well as increased aluminium and/or heavy metals toxicity as lowered soil pH can increase solubility of certain toxic chemicals, resulting both direct plant toxicity, decreased soil microbial diversity, and equally important in terms of relevance to human consumption, accumulation of toxic metals by the plant (Yan et al, 2021;Naz et al, 2022).…”
Section: Factors That Influence Soil Microbial Communities Of Tea Gar...mentioning
confidence: 99%